[OP.5C.07] THE LINK BETWEEN CARDIORESPIRATORY FITNESS AND CARDIAC AUTONOMIC NERVOUS SYSTEM IN OBESE YOUTH. (September 2017) - Redon, P.; Grassi, G.; Redon, J.; Álvarez, J.; Lurbe, E.
Abstract : Objective: Over the last decades the prevalence of obesity in children and adolescents has increased worldwide. This fact affects health expectancy and quality of life and then, assessment of cardiovascular risk factors has been emphasized. Among cardiovascular risk factors in adults, the relevance of cardiorespiratory fitness has been highlighted by the American Heart Association (AHA, Circulation 2016). To assess the cardiorespiratory fitness and its relationship with the cardiac autonomic neural activity, a marker of early cardiometabolic risk, in youths with abnormally increased body weight. Design and method: Sixty-four overweight and obese subjects, 9 to 17 years, of both sexes, stratified according to the international body mass index cut-off, were enrolled. Continuous electrocardiogram was recorded during 15 minutes in resting and supine conditions, and afterwards heart rate variability was analysed in the time and frequency domain as well as non-linear dynamics. In addition, cardiorespiratory fitness in effort conditions was assessed (VO2peak). Results: Among the obese youths, cardiorespiratory fitness was the lowest in severe obese despite that no significant differences were observed regarding heart rate nor heart rate variability in time and frequency domain. A positive and significant relationship, independent of the degree of obesity, pubertal stage and breathing rate under resting conditions, were observed between cardiorespiratory fitness (assessed by VO2peak) and sympatho-vagal balance, estimated by standard deviation of the NN interval (SDNN: r = 0.268, p < 0.05) and the long term variation using the Poincaré plot (PS1: r = 0.275, p < 0.05; PS2 r = 0.273, p < 0.05). Conclusions: The key finding of the present study was the presence of a link between cardiorespiratory fitness and cardiac autonomic nervous system activity, independent of the degree of obesity. This emphasises that cardiorespiratory fitness can be a relevant tool in the assessment of early cardiovascular risk in obese youths.